Alcohol Use Disorder and the Gut–Brain Axis: A Narrative Review of the Role of Gut Microbiota and Implications for Treatment - Shikha Shukla; Cynthia L. Hsu (Microorganisms)
Alcohol use disorder (AUD) affects millions of people worldwide and can lead to deleterious physical and social consequences. Recent research has highlighted not only the effect of alcohol on the gut microbiome, but also the role of the gut microbiome and the gut–brain axis in the development and maintenance of alcohol use disorder. This review provides an overview of the reciprocal relationship between alcohol consumption and the gut microbiome, including the effects of alcohol on gut microbial composition, changes in gut microbial metabolites in response to alcohol consumption, and how gut microbial metabolites may modulate alcohol use behavior. We also discuss the gut-mediated mechanisms of neuroinflammation that contribute to and result from AUD, including disruption of the intestinal barrier, toll-like receptor signaling, and the activation of glial cells and immune cells. Finally, we review the current evidence on gut microbial-directed therapies for AUD and discuss the implications of this research for our understanding of the pathophysiology of AUD and future research directions.